Balance of payment crises in emerging markets: how early were the “early” warning signals? - Matthieu Bussière (European Central Bank (ECB), 2007)
Although many papers have already proposed empirical models of currency crises, the timing of such crises has received relatively little attention so far. Most papers use indeed a static specification and impose the same lag structure across all explanatory variables. This, by construction, prevents from specifically timing the crisis signals sent by the leading indicators. The objective here is to fill this gap by considering a set of dynamic discrete choice models. The first contribution is to identify how early in advance each explanatory variable sends a warning signal. Some indicators are found to signal a crisis in the very short run while others signal a crisis at more distant horizons. The second contribution is to show that state dependence matters, albeit mostly in the short run. The results have important implications for crisis prevention in terms of the timeliness and usefulness of the envisaged policy response.
Keywords: C23; F15; F14; 330; balance of payments; currency crises; debt ratios; Dynamic discrete choice; emerging markets; panel data; sudden stop; Währungskrise; Schwellenländer; Außenwirtschaftliches Gleichgewicht; Wirtschaftsindikator; Schwellenländer